RANCANG BANGUN MESIN HOT PRESS LIMBAH PELASTIK SERTA PERHITUNGAN KONSUMSI ENERGI PENCETAKAN - Wiawan Adhi Guna, I Putu Gede; Indra Partha, Cokorde Gede; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUM, 2024)
The issue of waste, particularly plastic waste, remains a challenging problem without a definitive solution. Plastic waste, especially that made from High-Density Polyethylene (HDPE), takes an extensive amount of time to decompose. Currently, plastic recycling machines are priced in the hundreds of millions, making them less accessible. Therefore, there is a need for affordable machines that function effectively alongside existing ones. This research introduces a hot press machine for recycling HDPE plastic. The hot press machine is capable of recycling HDPE plastic waste and offers the advantages of being portable, compact in size, and cost-effective. Following the design phase, the machine is capable of producing plastic boards with a thickness of 1 cm, utilizing 3.7 kg of plastic, and requiring a molding time of 2 hours and 15 minutes at a pressure of 4.36 MPa.Subsequent testing involved analyzing three factors to determine the significant influence of factor A (heating temperature) and factor B (heating time) on energy consumption. The goal was to identify the interaction that yielded the smallest average energy consumption.